FROM RESEARCH TO IMPACT: Towards just and resilient agri-food systems - CGIAR GENDER Impact Platform (CGIAR GENDER Impact Platform, 2023)
The international research conference “From research to impact: Towards just and resilient agri-food systems” will address the gender and social inequalities that lie at the heart of food systems. The conference aims to promote the sharing of cutting-edge knowledge on gender and inclusion in agri-food systems to help bridge the gap between research and practice and foster gender-equal and socially inclusive, resilient food systems. This conference will catalyze scientific exchanges and dialogues among researchers from diverse types of organizations and will create opportunities to engage with knowledge users working towards the shared goal of food systems transformation. Strengthening social networks and building partnerships for impact will also be actively pursued throughout the conference